Relevansi Istihsan Dan Istishab Di Masa Kini Dan Mendatang - Fitriani Saragih; Sudirman Suparmin; Tuti Anggraini (CERED Indonesia Institute, 2022)
As the times develop, the problems that occur in society are increasingly complex and not all problems that occur can be explained by the Qur'an and Sunnah. However, because ijmak is difficult to do, the scholars carry out istimbath of Islamic law in the form of istihsan and istishab. Istihsan and istishab as sources and methods of law are still debated, there are some scholars who accept it and some scholars who reject it. This study aims to see whether istihsan and istishab are still relevant to current and future economic conditions. The method used is the library method and the results of this study will provide an overview of the relevance of istihsan and istishab today and in the future.